Etiology of isolated terminal ileal ulcers in symptomatic patients - Thapa, Suresh; Karki, Binod; Khadka, Dibas; Karki, Sanjit; Shrestha, Roshan; Thapa, Jiwan; Baral, Shankar; Yadav, Bhuwneshwer; Shrestha, Ramila; Poudel, Bidhan Nidhi (Nepal Journal of Medical Sciences, 2019)
Introduction: Isolated terminal ileal ulcers (ITIUs) are being frequently encountered by the clinicians with the increasing numbers of ileal intubation during colonoscopies. This study was aimed at finding the etiologies of these ulcers in symptomatic patients and their association with various clinical features. Methods: This was a hospital based prospective, observational, descriptive study performed on all consecutive patients who underwent ileocolonoscopy for various gastrointestinal symptoms between 1 July 2018 and 30 June 2019. Clinical, endoscopic and histopathological findings were analyzed to determine the etiology of ITIUs in symptomatic patients. Statistical analysis was done by SPSS 20. Results: Among 60 (7.67%) of 782 symptomatic patients who had ITIUs on ileocolonoscopy, specific etiologies were established in 28 (46.67%) of them. Intestinal TB was the most common specific diagnosis, which was seen in 18 (30%) patients. Chronic abdominal pain with or without chronic diarrhea was the most common indication for ileocolonoscopy. Conclusions: Specific etiologies like tuberculosis, Crohn’s disease, NSAID-induced ulcer and intestinal spirochetosis were seen in 28 (46.67%) of patients with isolated terminal ileal ulcers. The most common clinical features were chronic abdominal pain (65%) and abdominal pain with diarrhea (16.7%). No clinical presentation was significantly associated with any specific etiology, thus emphasizing the need for routine ileal intubation and tissue sampling for histopathological examination in all symptomatic patients undergoing colonoscopy.